MENINGKATKAN PEMAHAMAN BERMAIN MUSIK KOLINTANG SISWA SMP ANAK TERANG SALATIGA MELALUI PENDEKATAN AKOR ARAH - Soegiarto Hartono (Abdi Seni, 2024)
This community service aims to introduce a new approach to teaching musik that emphasizes the understanding that the essence of playing musik is to make measured movements in achieving the right target at the right time and cooperation in achieving balance (harmony). This approach goes beyond the need for the sense of hearing or musikal talent, thus opening up opportunities for everyone to learn musik, regardless of their talent. This activity was implemented at SMP Anak Terang Salatiga, with interactive and participatory learning methods that involve students in the teaching and learning process. Results show that this approach is effective in improving students' understanding and ability to play musik, as well as increasing their interest in music